RECEPTION POLICIES OF VENEZUELAN MIGRATION: A COMPARISON OF BORDER AREAS IN COLOMBIA, PERU, BRAZIL, THE UNITED STATES, AND CHILE - Paula Gomes Moreira; Maurício Kenyatta Barros da Costa (Revista Tempo do Mundo)
The goal of this article is to examine the exodus of Venezuelan citizens from a human mobility perspective, aiming to contribute to the discussion on their ongoing humanitarian crisis. It evaluates the reception policies in Colombia, Peru, Brazil, the United States, and Chile, countries that have recently received the most contingent of migrants. The comparative analysis reviews the institutional measures implemented in each country to identify the unique aspects of the selected group, particularly in border areas. Ultimately, the cases demonstrate that reception policies include regularization practices, the issuance of humanitarian visas, and specific programs for access to essential services. At the borders, there are similarities in migratory pressures and coordinated responses among the various agencies of the receiving governments.